Percepção de risco e representações sociais a respeito da implementação do Reator Multipropósito Brasileiro (RMB) em Iperó - SP - Ayllon, Rafaella Menezes [UNIFESP] (2017)
What differs a nuclear reactor for research purposes from those built for power generation? Is there a real reason for population concern about an accident in the implementation of a nuclear reactor for research purposes? On the other hand, what are the benefits that the implementation of this type of reactor can cause for the population in general? What about the socio-environmental impacts, do they really exist? These are important questions to be answered, aiming to clarify the population about nuclear projects, such as the implementation of the first Brazilian Multipurpose Nuclear Reactor (RMB) at the Aramar Experimental Center, located in the city of Iperó, São Paulo. We believe it is important because the reactor has the purpose of producing radioisotopes to be applied in health and industry, therefore with a strong social appeal. However, it is well known that public opinion about Nuclear Technology (TN) has changed seriously during its history, both from a scientific and a political point of view, however, it is undeniable that it has been more successful in the area of science than in the area of politics. It has suffered from periods of strong rejection due to negative events, such as the accident in Fukushima in 2011. In the case of the RMB, public hearings were held in the municipalities of Iperó, Sorocaba and Sao Paulo and whom were published in newspapers, electronic newspapers, electronic websites, television networks, as well as banners with information of the date, place, time and purpose of the audiences located in those cities. Despite of those facts, in general, most of the population did not accept the project. There was also little involvement of the regional schools in the debate about the implementation of the RMB, which generates concerns because education creates the possibility and has the importance to reduce the negative perception of risk as well as negative attitudes of the population towards the nuclear issue. Thus, education might promote greater acceptance of the reactor in the municipality. In this perspective, the objective of this study was to investigate the perception of risk (PR) and social representations (RS) of the population of Iperó municipality, SP, in relation to the implementation of RMB through a semi-structured questionnaire. As part of the results obtained, there was a negative RS and a high PR among the participants, a low level of involvement of the participants with the implementation of the RMB and little visualization of the benefits that the reactor can bring to the site. Therefore, it demonstrates the need to amplify and improve the communication between project managers and the general public.